Enhanced high-frequency microwave absorption of Fe3O4 architectures based on porous nanoflake. Issue 17 (1st December 2017) - Wang, Xiaoliang; Liu, Yanguo; Han, Hongyan; Mølhave, Kristian; Sun, Hongyu
Abstract: Hierarchical Fe3 O4 architectures assembled with porous nanoplates ( p -Fe3 O4 ) were synthesized. Due to the strong shape anisotropy of the nanoplates, the p -Fe3 O4 exhibits increased microwave resonance towards high frequency range. The improved microwave absorption properties of the p -Fe3 O4, including dielectric loss and magnetic loss, are attributed to the enhanced electric polarization and interfacial polarization induced by oxygen vacancies and high surface area.